2008
DOI: 10.1038/jhh.2008.124
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum concentrations of persistent organic pollutants and prevalence of newly diagnosed hypertension: results from the National Health and Nutrition Examination Survey 1999–2002

Abstract: Epidemiological studies have suggested a link between exposure to persistent organic pollutants (POPs) and hypertension. Cross-sectional associations of serum POP concentrations with the prevalence of newly diagnosed hypertension were investigated in 524 adult participants aged >/=40 years in the National Health and Nutrition Examination Survey 1999-2002. Twenty-one POPs (three polychlorinated dibenzo-p-dioxins (PCDDs), three polychlorinated dibenzofurans (PCDFs), five dioxin-like polychlorinated biphenyls (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 31 publications
3
47
0
4
Order By: Relevance
“…More recently, other studies have shown that residents living near areas contaminated with POPs had greater incidences of heart diseases and hypertension than those living in relatively clean areas [9,17]. Other studies using The NHANES data added to evidence by showing an association between selfreported cardiovascular diseases and hypertension with exposure to both dioxin-like PCBs and non-dioxin-like PCBs [8,18]. The higher serum levels of OC pesticides in subjects with PAD compared with those without PAD in this study corroborate the findings of other reports.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, other studies have shown that residents living near areas contaminated with POPs had greater incidences of heart diseases and hypertension than those living in relatively clean areas [9,17]. Other studies using The NHANES data added to evidence by showing an association between selfreported cardiovascular diseases and hypertension with exposure to both dioxin-like PCBs and non-dioxin-like PCBs [8,18]. The higher serum levels of OC pesticides in subjects with PAD compared with those without PAD in this study corroborate the findings of other reports.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies indicate that PCBs cause endothelial cell dysfunction, hyperlipidemia and hypertension that are corner stones in the development of atherosclerosis [2][3][4][5][6][7]. In humans, PCB exposure has been associated with several intermediate risk factors for CVD such as hypertension [8][9][10][11], hyperlipidemia [9,12,13], atherosclerosis [14], and type 2 diabetes [15,16]. Recent prospective epidemiological studies indicate associations with increased risk of stroke [17,18], while studies exploring the association with incidence of myocardial infarction are almost lacking [19].…”
Section: Introductionmentioning
confidence: 96%
“…Everett et al [13] reported that concentrations of seven of 10 PCB congeners examined were significantly correlated with hypertension, and that those congeners with dioxinlike activity had the highest odds ratios (ORs). Ha et al [14] examined 21 POPs (three dioxins, three furans, five dioxin-like PCBs, six nondioxin-like PCBs, and four organochlorine pesticides). They reported a statistically significant positive relationship between levels of dioxins or furans and hypertension in women, and weaker but still significant relations with both dioxin-like and nondioxin-like PCBs in men.…”
Section: Introductionmentioning
confidence: 99%